An integrative miRNA-mRNA expression analysis identifies miRNA signatures associated with SOD1 and TARDBP patient-derived motor neurons - Dash, Banaja Priyadarshini; Freischmidt, Axel; Weishaupt, Jochen H.; Hermann, Andreas (Human molecular genetics, 2024)
MicroRNAs (miRNAs) are a subset of small non-coding single-stranded RNA molecules involved in the regulation of post-transcriptional gene expression of a variety of transcript targets. Therefore altered miRNA expression may result in the dysregulation of key genes and biological pathways that has been reported with the onset and progression of neurodegenerative diseases, such as Amyotrophic lateral sclerosis (ALS). ALS is marked by a progressive degeneration of motor neurons (MNs) present in the spinal cord, brain stem and motor cortex. Although the pathomechanism underlying molecular interactions of ALS remains poorly understood, alterations in RNA metabolism, including dysregulation of miRNA expression in familial as well as sporadic forms are still scarcely studied. In this study, we performed combined transcriptomic data and miRNA profiling in MN samples of the same samples of iPSC-derived MNs from SOD1- and TARDBP (TDP-43 protein)-mutant-ALS patients and healthy controls. We report a global upregulation of mature miRNAs, and suggest that differentially expressed (DE) miRNAs have a significant impact on mRNA-level in SOD1-, but not in TARDBP-linked ALS. Furthermore, in SOD1-ALS we identified dysregulated miRNAs such as miR-124-3p, miR-19b-3p and miR-218 and their potential targets previously implicated in important functional process and pathogenic pathways underlying ALS. These miRNAs may play key roles in the neuronal development and cell survival related functions in SOD1-ALS. Altogether, we provide evidence of miRNA regulated genes expression mainly in SOD1 rather than TDP43-ALS.
Online verfügbar: 27. April 2024
Gesehen am 24.10.2024